Pertumbuhan dan Ketimpangan Pembangunan Ekonomi (Studi Kasus: Provinsi Aceh) - Imilda; Sufyan; Rahmi Hajriyanti (Jurnal EMT KITA, 2022)
This study aims to analyze economic growth and development in the District/City of Aceh Province for the period 2012 to 2016 and identify the economic growth of the District/City in Aceh Province which has a significant influence. The data used in this study is 5-year panel data from 23 regencies/cities of Aceh Province from 2012 to 2016, while the object of this research is the development of economic development in each region, regional economic development and the factors that influence it. Based on the results of growth and the Aceh Province's inter-regional economic development in Aceh Province, it can be ascertained that 1) Inequality of economic development in Aceh Province Regency/City which is calculated using Entropy for the 2012-2016 Period shows an increase, 2) The order of Aceh Regency/City which has a high growth value minus / negative namely City. Lhokseumawe, Regency. North Aceh and the District. East Aceh, 3) economic growth and income which were analyzed using Theil Entrophy Index showed an increase every year from 2012-2016 in the City. Subulussalam, Langsa City and Sabang City, 4) Sources of economic growth in Aceh Province are partly generated from economic sectors such as agriculture sector, implementation sector, industrial sector, plantation sector, transportation sector, information, and communication sector, and 5) Based on In the test using a linear trendline, there are 7 regencies/cities out of 23 regencies/cities in Aceh Province, namely regencies. Simeulue, District, Aceh Besar, District. Southwest Aceh, Sabang City, Langsa City, Bener Meriah Regency, and Subulussalam City which deserve R2 close to 1 and are relatively strong, namely the independent variable explains the variable.